Design and Analysis of the US ITER Central Solenoid Module Lifting Fixture. (17th November 2019) - Morris, Eric; Freudenberg, Kevin F.; Myatt, Leonard; Reagan, Travis; Reiersen, Wayne
Abstract: The central solenoid (CS) consists of six large high field superconducting magnets (also known as modules) approximately 4 m in diameter and 2 m tall that weigh approximately 120 tonnes each. These large and complex modules create challenges during assembly of the CS that require the development of custom assembly tooling such as the CS lifting fixture. The CS module lifting fixture is designed to lift and stack the six CS modules in the assembly building on the ITER site. Because of its unique design, fabrication, and assembly features, no lifting attachments could be incorporated within or under the CS modules. This limitation motivated the development of a friction-based lift fixture. The design and evaluation of the CS module lifting fixture considered both worker safety and investment protection, and the assessments were performed to international codes and standards. The CS module lifting fixture consists of two principal subassemblies: spider assembly and ring weldment. These subassemblies allow the frictional force to be augmented by the mechanical advantage of shallow-angle wedges. Large radial preloads created by both screw jack assemblies and the weight of a CS module develop frictional forces capable of performing a lift with a safety factor of at least 2. The design effort resulted in the use of low friction linear bearings on angle surfaces to ensure constant pressure, integrated jacks for pretensioning the fixture prior to lifting, and load pin strain gauges for monitoring the normal force. Testing of various materials and surface treatments led to the selection of laminated aluminum and rubber pads as the friction interface on the CS lifting fixture side and a grit-blasted Nitronic 50 stainless steel band on the CS module side. A redundant lifting method using the module slings between the spider and module is also utilized after the initial friction lift. The CS lifting fixture provides a safe and reliable solution for lifting and stacking the CS module during assembly.